INSPIRASI SUFISME AL-ARABI UNTUK KESEHATAN MENTAL - Qonita Masyithah; Nunu Burhanuddin (ADISAM PUBLISHER, 2023)
This comprehensive article elucidates the inspirational potential of Ibn Arabi's Sufi teachings in the context of enhancing mental health. Through an exploration of the concept of unity of existence, readers are invited to discover tranquility in connection with God and the surrounding environment. The described practices of Sufi meditation provide practical tools for alleviating stress and increasing self-awareness. The concept of self- acceptance emerges as a key point, offering a robust foundation for managing psychological pressure and building resilient mental health. The interconnection of spirituality with mental health is positioned as a potential source of support and tranquility. Delving into the legacy of Sufi wisdom, this article embraces a new perspective on mental health, urging readers to open themselves to the potential for growth and healing through the teachings of Ibn Arabi.